(untitled) (MAUSAM, 1961)
The monthly and annual frequency of days of thunder in India are presented in the form of charts with brief descriptions, The most thundery areas in the C9untry are Assam (extreme northeastern Assam with the highest annual frequency exceedmg100 days), Bengal, Orissa and the adjoining areas of Bihar. The least frequency (less than 10) occurs in western Saurashtra and Kutch Kendrew’s remarks on frequency of thunder in India have been discussed.